Endoscopic Resection of Esophageal Lymphangioma Incidentally Discovered. Issue 3 (1998) - Scarpis, M.; De Monti, M.; Pezzotta, M. G.; Sonnino, D.; Mosca, D.; Milani, M.
Abstract : A pedunculated lymphangioma of the esophagus was unexpectedly discovered during an endoscopic investigation performed for epigastric pain in a patient affected by diabetic arteriopathy treated with antiplatelet drugs. The patient neither complained of dysphagia nor other symptoms related to the presence of the lymphangioma which therefore can be considered as an endoscopic "incidentaloma". The lesion was removed endoscopically and a follow up, 6 months later, showed no scar or recurrence. The authors present this case both for the extreme rarity of this lesion and for the evidence of low-medium grade dysplasia in the overlying mucosa, particularly since it is only case ever noted in literature. This aspect suggests that, even if malignant degeneration of these lesions has never been observed, their endoscopic removal is recommended. However, when endoscopic procedures are not feasible, thoracotomic surgical exeresis should be only considered for obstructing and symptomatic lesions; an accurate endoscopic and bioptic follow up can be useful for asymptomatic lesions.